Environmental Influence on the Use of Abusive Language and Solutions through the NABA Program at SDN-SN Kuripan 2 - Fatihah, Dea Amani; Kuramah, Najwa; Faulina Barus, Cesillia; Wulandari, Chairunnisa; Rizqy Ramadhani, Muhammad; Laily Anggraini, Noor; Ilma, Rosiha; Hidayat, Ari (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2025)
The surrounding environment is one of the primary factors influencing children's behavior. The environment has the potential to exert both positive and negative influences. This study aims to explore the impact of the surrounding environment on the behavior of elementary school students. The research employs a qualitative descriptive approach, with data collected through observation and interviews. Field findings indicate that negative environmental influences can lead to undesirable behaviors among students, such as the tendency to use inappropriate language in communication. This study is expected to be followed up with the implementation of the